Land management regulation as an instrument for planning in Ukraine - Dorosh, O.; Buriak, R.; Kupriyanchyk, I. (Land Management, Cadastre and Land Monitoring, 2017)
The presence of problems in the territorial management of land indicates that the system of state and municipal management does not meet the modern requirements of sustainable (balanced) development. The explanation is simple - if the planning of the development of territories of settlements takes place on the basis of approved urban planning documentation (master plans), then the territory of land tenure and land use outside their borders is notfully covered by development of land management documentation. In this regard, the importance of the development and implementation of land management regulations at the practical level as an important land-use planning tool is substantiated. Essential and meaningful signs of the concepts of "urban planning regulations", "land management regulations" for conducting researchesare found. The National Standard defines the concept of urban planning regulations, such as the use of land plots, established within the respective territorial zones and defines the types of preferential and related use of land, the limits of permitted construction, reconstruction of construction objects and is used in the design, construction and subsequent operation of Objects. The draft law of Ukraine "On zoning of land" proposed the definition of land management regulations as approved in accordance with the established procedure text materials, that determine the parameters of the permitted use of land (land use regime) and acceptable changes in these parameters. However, this draft law is not harmonized during the 10-year period at the state level, therefore the proposed terms and definitions do not fully comply with modern requirements. Therefore, it is proposed to supplement them with other terms and definitions. Based on the research carried out, the author’s definition of land management regulations should be understood as the procedure for land use, which is established within the respective territorial zones, with the definition of the legal regime of the territory of land use, which specifies the boundaries of the land plot, restrictions on the land use and the types and parameters of permitted land use, types of predominant and concomitant use of land plots, which indicate prohibited activities and responsibilities in relation to taking certain actions. It’s established that land management regulations should become an integral part of the land management project on land zoning. For this purpose, a methodological approach to the formation of the legal regime of land use in land zoning according to their categories is proposed. The given division of land by types and subtypes of land use will allow to properly form territorial restrictions on land use with subsequent differentiation to land plots. A combination of urban planning and land management regulations will contribute to the achievement of sustainable (balanced) land use. Key words: land use planning, urban planning regulations, land management regulations, land categories, land zoning, types of land use